Density Regimes and Heat Flux Deposition in the WEST Shallow Divertor Configuration. Issue 4 (June 2014) - Bufferand, H.; Bucalossi, J.; Ciraolo, G.; Fedorczak, N.; Ghendrih, P.; Leybros, R.; Marandet, Y.; Serre, E.; Tamain, P.
Abstract To support ITER divertor design, the WEST project on Tore Supra aims at studying high heat fluxes on tungsten monoblock during long pulses. In that persective, a particular attention is paid to simulate the edge plasma interaction with complex PFCs using the transport code SOLEDGE2D‐EIRENE. The plasma response to a heating and puffing scenario is described as well as the so‐called divertor density regimes, characterizing the operational domain of the WEST divertor. These results are compared for two different magnetic configurations: a semi‐open double null divertor with the X‐point away from the target plates and a shallow divertor configuration with the X‐point close to the targets. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)